Where humans and spirits meet : the politics of rituals and identified spirits in Zanzibar. - Larsen, Kjersti (Social identities ;, 2008)
Zanzibar, an island of the East African coast, with its Muslim and Swahili population, offers rich material for this study of identity, religion, and multiculturalism. This book focuses on the phenomenon of spirit possession in Zanzibar Town and the relationships created between humans and spirits; it provides a way to apprehend how society is constituted and conceived and, thus, discusses Zanzibari understandings of what it means to be human -- Présentation de l'éditeur.